Pengaruh Kadar Coupling Agent Maleated Natural Rubber Terhadap Morfologi Dan Sifat Karet Alam Thermoset Dengan Filler Abu Sawit/Carbon Black - Andri Mulia; Bahruddin Bahruddin; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Maleated Natural Rubber (MNR) is a coupling agent which serves to facilitate mixing natural rubber and filler. This research aims to determine the effect of concentration MNR on the morphology and properties of thermoset rubber with fly ash/carbon black as filler. MNR content used were 2 phr 3 phr and 5 phr (per hundred rubber). Mastication process is carried out using a roll mill at room temperature, roll rotational speed of 20 rpm, and the overall time of the manufacture of compound ± 50 minutes. Constant variable is fly ash/carbon black, paraffin as plasticizer, ZnO as activator, stearic acid as co-activator, MBTS as accelerator, TMQ as anti-degradant, and sulfur as curative agent. The ratio of mass hybrid filler fly ash/carbon black used were 0/100; 30/70; 50/50; 70/30 and 100/0. Vulcanization process was carried out at a temperature of 150 °C and pressure of 50 kgf/cm2. Mechanical properties test includes tensile strength, elongation at break and elastic modulus using ISO 527-2 type 5A standard with a universal testing machine. Morphology test was carried out using a scanning electron microscope (SEM) and other parameter test was water absorption resistance. The result showed that coupling agent MNR affect the nature of thermoset and rubber. Best morphology image shows more evenly distributed filler, and interaction of filler and rubber formed quite homogeneous and uniform. The best mechanical properties obtained at 3 phr MNR with filler ratio of fly ash/carbon black 50/50 with a tensile strength of 18,147 MPa, elongation at break 1402.8 % and elastic modulus of 0.7688 MPa.Keywords : fillers hybrid , MNR, natural rubber, thermoset rubber.